Managing acute ischaemic stroke in a small island developing state: meeting the guidelines in Barbados - Asanchia S. Harewood-Marshall; Leslie S. Craig; Tanya P. Martelly; David O. C. Corbin; Lauren Maul; Damani McIntosh-Clarke; Tracey Blackman; Kenneth S. George; Anselm J. M. Hennis; Ian R. Hambleton; Angela M. C. Rose (BMC, 2018)
Abstract Background We describe hospital-based management of acute ischaemic stroke patients in 2010-2013 in Barbados, by comparing documented treatment given in the single tertiary public hospital with international guideline recommendations. Methods Evidence-based stroke management guidelines were identified through a systematic literature search. Comparisons were made between these guidelines and documented diagnostic practice (all strokes) and prescribed medication (ischaemic stroke only), using a combination of key informant interviews and national stroke registry data for 2010-2013. Results Several published international guidelines for the acute management of ischaemic stroke recommended patient management in a dedicated stroke unit or nearest hospital specialised in stroke care. Further, patients should receive clinical diagnosis, CT brain scan, specialist evaluation by a multidisciplinary team and, if eligible, thrombolysis with alteplase within 3-3.5 h of symptom onset. Subsequent secondary prophylaxis, with a platelet aggregation inhibitor and a statin was advised. Barbados had no stroke unit or stroke team, and no official protocol for acute stroke management during the study period. Most of the 1735 stroke patients were managed by emergency physicians at presentation; if admitted, they were managed on general medical wards. Most had a CT scan (1646; 94.9%). Of 1406 registered ischaemic stroke patients, only 6 (0.4%) had been thrombolysed, 521 (37.1%) received aspirin within 24 h of admission and 670 (47.7%) were prescribed aspirin on discharge. Conclusions Acute ischaemic stroke diagnosis was consistent with international recommendations, although this was less evident for treatment. While acknowledging the difficulty in implementing international guidelines in a low-resource setting, there is scope for improvement in acute ischaemic stroke management and/or its documentation in Barbados. A stroke unit was established in August 2013 and written clinical protocols for acute stroke care were in development at the time of the study; future registry data will evaluate their impact. Our findings have implications for other low-resource settings with high stroke burden.